Exploring the Teaching of English in an inclusive classroom: a Case Study - Pramesti, Athiyyah Shabina Auzi; Khairiyah, Ninda Anisatul; Rahmah, Eve Salsabila; Putri, Navisha Ayu Pristya Ikhe; Setyowati, Lestari (Universitas PGRI Madiun, 2023)
This study has three aims. The first was to investigate the program that support the inclusive education at SMP Laboratorium UM. Secondly, the study was aimed at investigating how the teacher teaches English in inclusive classrooms, and the common challenges faced by the English teacher in teaching an inclusive classroom. The researchers used qualitative research using the case study method with two main instruments, namely interviews and observations. The participants involved in this research were an inclusive education school coordinator, an English teacher in inclusive classrooms, and students with special needs. The data were collected in two weeks via two interviews and two field observations. The data collected were in the form of tape recording, field notes, pictures, and videos. Those data were qualitatively analyzed to answer the research questions. The result of the study is categorized in three main points. First, the school offers program that support the implementation of inclusive education, such as self-development program, and extra courses that facilitate SEN students’ development of basic life skills. There are ten classes assigned to accommodate at least one special need student in each class. Second, when it comes to teaching English in inclusive classrooms, the teachers showed a lack of specific strategies, but they used game-based technology like Kahoot to make enjoyable learning. The teachers faced challenges, like handling tantrums and moody students. Third, the result also shows that patience and sincerity are important when teaching SEN students.